2006
DOI: 10.1111/j.1467-954x.2006.00616.x
|View full text |Cite
|
Sign up to set email alerts
|

'When I'm in the Garden I Can Create My Own Paradise': Homes and Gardens in Later Life

Abstract: This paper brings together recent work on later life and considers the effects of ageing in relation to participation and interest in gardening. Whilst there is considerable research and literature on issues such as health, housing, and social care, the significance of the garden in process of home-making is less well understood. Using qualitative data from the Mass Observation Data Archive, key physical, psycho-social processes that impact on the use of the garden and gardening activities are examined. It wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 35 publications
2
91
0
1
Order By: Relevance
“…The home then is always being made and re-made by individuals later in life, particularly as individuals begin to face the challenges of ageing (Bhatti 2006). In returning to experiences post retirement, Mowl et al (2000) argue that rather than feeling entirely disempowered, men are also presented with an opportunity to actively negotiate their relationships with the home, which they tend to construct around notions of femininity and old age.…”
Section: Ageing Masculinities and The Homementioning
confidence: 99%
“…The home then is always being made and re-made by individuals later in life, particularly as individuals begin to face the challenges of ageing (Bhatti 2006). In returning to experiences post retirement, Mowl et al (2000) argue that rather than feeling entirely disempowered, men are also presented with an opportunity to actively negotiate their relationships with the home, which they tend to construct around notions of femininity and old age.…”
Section: Ageing Masculinities and The Homementioning
confidence: 99%
“…Gross and Lane (2007), in their study of domestic gardens and gardening, explore how the development of a garden can "embody the individual's existing interests, passions, preferences and characteristics, signifying identity …" (p. 236). Bhatti (2006) also takes up this theme exploring the place of gardens as part of homemaking in the life of older people, and their importance in terms of memories, identity and self esteem, and embodied practice. These themes -perhaps not surprisingly given their history of immigration -are also explored in a number of studies from New Zealand and Australia in relation to migrant identities and gardens; for example Graham and Connell (2006) studied Vietnamese and Greek migrants with regard to how their identities were reflected in evolving relationships with gardens; Li et al (2010) investigated gardening as a means of forging a new sense of self and place in Chinese immigrants' adoptive country; and Morgan et al (2005) focused their research on the backyards of immigrants to Australia and how, in growing 'authentic homeland food', they "symbolically recapture the homeland in the new land"(p. 97).…”
Section: Gardens Allotments Food and Identitymentioning
confidence: 99%
“…61.8% of garden owners were retired and the rest of them were employed. This age ratio could be explained as a period of independent, full and active life that encourages people in the gardening activity (Bhatti, 2006), however the survey showed that most of the owners started gardening when they were in their 40s. Gardens were open from few hours to the whole year long and the length they have been listed by the NGS varying from fifty years to a few days.…”
Section: Six Reasons To Open a Garden To The Publicmentioning
confidence: 99%
“…GO60+ described how she has been dealing with her partner's death with garden opening: 'It brought me into a new circle of friends, but I also try to find a way of living after a 56 year marriage, being free to do what I want. ' The physical changes as people get older can encourage them into physical activity that can help to take advantage of each day (Bhatti, 2006). Many elderly owners stated that gardening became a form of physical exercise, opening new possibilities to resist the image of inactive and senile body.…”
Section: Figurementioning
confidence: 99%